2014
DOI: 10.1186/1750-1326-9-1
|View full text |Cite
|
Sign up to set email alerts
|

Axonal BACE1 dynamics and targeting in hippocampal neurons: a role for Rab11 GTPase

Abstract: BackgroundBACE1 is one of the two enzymes that cleave amyloid precursor protein to generate Alzheimer's disease (AD) beta amyloid peptides. It is widely believed that BACE1 initiates APP processing in endosomes, and in the brain this cleavage is known to occur during axonal transport of APP. In addition, BACE1 accumulates in dystrophic neurites surrounding brain senile plaques in individuals with AD, suggesting that abnormal accumulation of BACE1 at presynaptic terminals contributes to pathogenesis in AD. Howe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
134
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 128 publications
(145 citation statements)
references
References 62 publications
10
134
1
Order By: Relevance
“…APOE-4 binds tightly to Aβ42 to clear it from neurons (30). As a result, soluble oligomeric Aβ levels are increased by APOE-4 (31). We found that concomitant changes of PrionD and AD occurred in patients who were between the ages of 50 and 85, the time when the APOE-4, a known risk factor for AD (32, 33), and neprilysin-α (34), the predominant degrading enzyme of Aβ40 and Aβ42 (35), exert their maximal effects on the development of AD (36).…”
Section: Discussionmentioning
confidence: 99%
“…APOE-4 binds tightly to Aβ42 to clear it from neurons (30). As a result, soluble oligomeric Aβ levels are increased by APOE-4 (31). We found that concomitant changes of PrionD and AD occurred in patients who were between the ages of 50 and 85, the time when the APOE-4, a known risk factor for AD (32, 33), and neprilysin-α (34), the predominant degrading enzyme of Aβ40 and Aβ42 (35), exert their maximal effects on the development of AD (36).…”
Section: Discussionmentioning
confidence: 99%
“…et al, 2012), RTN3 (Deng et al, 2013), Rab11 and Eps15 homology domain proteins (Buggia-Prevot et al, 2013, 2014; Udayar et al, 2013). The enhanced localization of BACE1 at synaptic sites is suggested to increase release of Aβ by the synaptic terminals and directly facilitates amyloid deposition in AD patients (Sadleir et al, 2016).…”
Section: Cellular Trafficking Of Bace1mentioning
confidence: 99%
“…Depletion of both GGA1 and GGA3 induces a rapid and robust elevation of BACE1, and such an effect will likely be interfered with by flotillin, which can compete with GGA proteins for binding to the same dileucine motif in the BACE1 tail (John et al, 2014). In neurons, BACE1 is targeted to both axons and dendrites, and its preferential transport to the axonal terminus versus somatodendrites can be regulated by altered levels of calsyntenin-1 (Steuble et al, 2012; Vagnoni et al, 2012), retromer vps35 (Wang et al, 2012a; Wen et al, 2011), RTN3 (Deng et al, 2013), Rab11, and Eps15 homology domain proteins (Buggia-Prevot et al, 2014; Buggia-Prevot et al, 2013; Udayar et al, 2013). The localization of BACE1 in synaptic sites can impact the processing of its substrates.…”
Section: Brief Overview Of Bace1mentioning
confidence: 99%